Local Development that Money Can't Buy: Italy's Contratti di Programma - Monica Andini; Guido de Blasio (European Regional Science Association (ERSA), 2012)
Local Development that Money Can't Buy: Italy's Contratti di Programma The paper evaluates the effectiveness of a major Italy's place-based policy (Contratti di Programma), through which the Government endorses and finances an industrialization plan proposed by private firms. By using as counterfactuals the areas that will be exposed to the same policy later in time, the study finds evidence of a positive impact on plants and employment, which is however confined to a small area (municipality) and does not extent to the local labor market area (aggregation of few neighbouring municipalities).
Keywords: R11; R58; C14; 330; Regional economic activity; location-based policies; program evaluation